Developing and Testing a Local Expert-Based Reading Process for Use to Examine Discrepancies Between Guidelines and Current Clinical Practices - Cases, Cécile; Gallini, Adeline; Lafont Rapnouil, Stéphanie; Bougon, Emmanuelle; Mathur, Anjali; Brismontier, Ariane; Taib, Simon; Sporer, Marie; Arbus, Christophe; Salles, Juliette (Frontiers in Psychiatry, 2021)
The use of relevant guidelines is critical in psychiatric clinical practice to ensure the homogeneity of the global care provided. Consequently, it is important to identify whether they are utilized successfully and, if not, why. This would enable pragmatic solutions to be agreed to improve the organization of care and the removal of any barriers to the guidelines' implementation. The first step in this process, before any exploration of the limitations of the guidelines themselves, involves a determination of whether they are actually applied in clinical practice. We therefore evaluated discrepancies between the guidelines relating to patients with borderline personality disorder and current practices in the psychiatric Emergency Department at Toulouse University Hospital. This was achieved using a reading process involving a panel of eight local experts who analyzed relevant medical files extracted from a database. They were guided by, and instructed to answer, six standardized questions in relation to each file to determine the method's feasibility. A total of 333 files were analyzed to determine whether, in the local experts' judgment, the care provided reflected current guidance. This reading process revealed substantial agreement (0.85%; Fleiss Kappa −0.69), which is a promising outcome and suggests that such methods could be used in future protocols. Moreover, the process is practical and reliable and requires very few materials.